ANALISIS EFEKTIVITAS PEMBIASAAN TADARUS SEBAGAI IMPLEMENTASI LITERASI DI SMPN 18 KOTA CIREBON - Mulyoto Mulyoto; Jaja Wilsa (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research was motivated by the beginning of the distance of students' habits from religious activities. The aim is to describe the effectiveness of habituation of tadarus Al Qur'an as the implementation of literacy in SMP Negeri 18 Kota Cirebon. The formulation of the problem from this study is how effective the habituation of tadarus Al Qur'an as the implementation of literacy in SMP Negeri 18 Kota Cirebon. The method used is descriptive qualitative, the researcher acts as a key instrument and describes the situation objectively or based on visible facts. The source of data from this study is teachers and students at SMP Negeri 18 Kota Cirebon with reference to indicators of the effectiveness of tadarus habituation as literacy implementation. The result of this study is an increase in students' positive attitudes related to congregational Zuhur prayer activities, Friday prayer activities, Friday infak, and memorizing short letters juz 30, as well as students' readiness to learn which is getting better, so that the habituation of tadarus as an implementation of literacy in SMP Negeri 18 Kota Cirebon is considered very effective.